BAHAYA MEROKOK PADA REMAJA DI SDN 1 SAWANG, KECAMATAN SAWANG, KABUPATEN ACEH UTARA - Ully Fitria; Ambia Nurdin; Dian Rahayu; Firjatullah; Ali Sumardi (PADMA, 2025)
This research aims to provide education on the dangers of smoking to adolescents at SDN 1 Sawang, Sawang District, North Aceh Regency. Smoking among adolescents is on the rise, which has negative impacts on physical and social health. This study uses a pre-experimental method with a One Group Pre-test and Post-test design to measure changes in adolescent knowledge after receiving counselling. This activity focuses on providing understanding about the dangers of smoking, the harmful chemical content in cigarets, and their impact on both active and passive smokers. The survey results show a significant increase in students' understanding of the negative impacts of smoking, particularly regarding the dangers to lung health, the risk of cancer, and the impact on those around them. Although some knowledge related to lung cancer remains stable, awareness of smoking cessation efforts and healthy behavior changes has increased. This education has proven effective in broadening students' horizons and raising their awareness of the dangers of smoking, with a particular focus on the adolescent age group, which is vulnerable to this habit.